Effect of ultrasound on goat cream hydrolysis by lipase: Evaluation on enzyme, substrate and assisted reaction. (August 2020) - Soares, Ariana de Souza; Leite Júnior, Bruno Ricardo de Castro; Tribst, Alline Artigiani Lima; Augusto, Pedro Esteves Duarte; Ramos, Afonso Mota
Abstract: The effect of ultrasound on lipase performance was studied in goat cream hydrolysis. Ultrasound (25 kHz, 22 W/L) was carried out on lipase and/or goat cream under different conditions (pH 6.0; temperature of 25, 40 and 55 °C; up to 5 h). As a pre-treatment, ultrasound did not induce goat cream hydrolysis, but slightly increased lipase activity (up to 12%), depending on the temperature and processing time (activation conditions at 25 °C/45 min and 40 °C/60 min). The fat hydrolysis assisted by ultrasound had higher hydrolysis rate when compared to conventional processing with an increase of 12% at 55 °C, 23% at 40 °C and 28% at 25 °C. The reaction temperature was an important parameter and lower temperatures improved the ultrasound effects. Possibly, these results are associated with the acceleration of mass transfer during ultrasound reaction, as well as the modifications promoted by ultrasound on the enzyme. Therefore, ultrasound was demonstrated as an interesting alternative to improve the goat cream hydrolysis by lipase. Highlights: Ultrasound pre-treatment increased lipase activity (up to 12%). Ultrasound did not cause goat cream hydrolysis. Ultrasound assisted hydrolysis rate increased up to 28%. Lower reaction temperatures showed the greatest ultrasound effects. Ultrasound emerges as an alternative to accelerate goat cream hydrolysis by lipase.